Dengue Epidemic THE POLICY DIRECTION OF DENGUE HAEMORRHAGIC FEVER DISEASE MANAGEMENT IN PALEMBANG CITY - Sekarrini, Cipta Putri; Sumarmi, Sumarmi; Bachri, Syamsul; Taryana, Didik; Giofandi, Eggy Arya; Purwaningsih, Endah; Iskarni, Paus; Umar, Iswandi (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
The aim of this study was to find out the spread of dengue hemorrhagic fever in the city of Palembang and then to create a policy direction for the prevention of dengue hemorrhagic fever in the city of Palembang. This study was undertaken in all areas of Palembang City. This sudy was descriptive with a quantitative approach. The sample of this study was dengue hemorrhagic fever patients who were found in each health center and community registered at the Palembang City Health Office using purposive sampling technique. Data collection consisted of observation data, the health office, interviews, documentation. Data analysis techniques used consisting geographic information system analysis and Analytical Hierarchy Process. The results indicated that the distribution of dengue hemorrhagic fever was of three levels, namely, high, medium, and low spread in 18 sub-districts in the city of Palembang. Furthermore, the policy directions given were: suppressing the rate of population growth, socializing about dengue hemorrhagic fever, improving drainage channels, eradicating mosquito nests, routine larvae inspection. on providing policy directions for dengue outbreaks starting from a basic understanding of the habitat structure of the aedes aegypti mosquito which will provide information related to the influence of the mosquito landscape in knowing the zoning of vulnerability to dengue outbreak transmission